Exploring the regulatory framework of sustainable finance In Malaysia: driving force for Esg institutional investors - Razali, Normarianie; Hassan, Rusni; Mohd Zain, Nor Razinah (IIUM Press, 2022)
Since the introduction of the United Nation Millennium Development Goals (2000) and Sustainable Development Goals (2015), sustainable finance had grown exponentially via the strong support of regulators introducing a framework to support the financing of sustainable development. Malaysian regulatory bodies played an active role in pushing the sustainable agenda via its capital market, banking, and takaful sectors. The introduction of the regulatory framework for sustainable finance aims to serve as a guide for the industry players to take part in sustainable investment in these sectors. Institutional investors as the largest asset owners and financial sector players are key to reshaping the Environment, Social and Governance (ESG) development. By employing qualitative library research method, an analysis is made specifically from documents, speeches, newspaper releases, peer-reviewed journals, and texts related to sustainable finance in Malaysia. This paper provides an oversight of the historical development and Malaysian experience in developing their sustainable finance regulatory framework in the capital market, banking and takaful sectors. This paper is of the view that the development of the sustainable framework plays a significant role that acts as a driving force for the ESG institutional investors in Malaysia.